# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime \prime \prime }-5 y^{\prime \prime }+4 y = -12 \,{\mathrm e}^{x}+6 \,{\mathrm e}^{-x}+10 \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime }+11 y^{\prime \prime }-14 y^{\prime }+10 y = -{\mathrm e}^{x} \left (\sin \left (x \right )+2 \cos \left (2 x \right )\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }-3 y^{\prime \prime }-4 y^{\prime }+4 y = 2 \,{\mathrm e}^{x} \left (1+x \right )+{\mathrm e}^{-2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y = \sinh \left (x \right ) \cos \left (x \right )-\cosh \left (x \right ) \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+5 y^{\prime \prime \prime }+9 y^{\prime \prime }+7 y^{\prime }+2 y = {\mathrm e}^{-x} \left (30+24 x \right )-{\mathrm e}^{-2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime }+7 y^{\prime \prime }-6 y^{\prime }+2 y = {\mathrm e}^{x} \left (12 x -2 \cos \left (x \right )+2 \sin \left (x \right )\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime }-y^{\prime }+y = {\mathrm e}^{2 x} \left (10+3 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime }-2 y = -{\mathrm e}^{3 x} \left (17 x^{2}+67 x +9\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y = {\mathrm e}^{2 x} \left (-3 x^{2}-4 x +5\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime \prime }+y^{\prime } = -2 \,{\mathrm e}^{-x} \left (6 x^{2}-18 x +7\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = {\mathrm e}^{x} \left (1+x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-2 y^{\prime \prime }+y = -{\mathrm e}^{-x} \left (3 x^{2}-9 x +4\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime \prime }-y^{\prime }-2 y = {\mathrm e}^{-2 x} \left (\left (23-2 x \right ) \cos \left (x \right )+\left (8-9 x \right ) \sin \left (x \right )\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-3 y^{\prime \prime \prime }+4 y^{\prime \prime }-2 y^{\prime } = {\mathrm e}^{x} \left (\left (28+6 x \right ) \cos \left (2 x \right )+\left (11-12 x \right ) \sin \left (2 x \right )\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime }+14 y^{\prime \prime }-20 y^{\prime }+25 y = {\mathrm e}^{x} \left (\left (2+6 x \right ) \cos \left (2 x \right )+3 \sin \left (2 x \right )\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime }-5 y^{\prime }+6 y = 2 \,{\mathrm e}^{x} \left (1-6 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime }-y^{\prime }+y = -{\mathrm e}^{-x} \left (4-8 x \right )
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime \prime }-3 y^{\prime }-y = {\mathrm e}^{-\frac {x}{2}} \left (2-3 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+2 y^{\prime \prime }+2 y^{\prime }+y = {\mathrm e}^{-x} \left (20-12 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime \prime }+y^{\prime }+2 y = 30 \cos \left (x \right )-10 \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-3 y^{\prime \prime \prime }+5 y^{\prime \prime }-2 y^{\prime } = -2 \,{\mathrm e}^{x} \left (\cos \left (x \right )-\sin \left (x \right )\right )
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }+6 x y^{\prime }-6 y = 2 x
\] |
✓ |
✓ |
|
\[
{}4 x^{3} y^{\prime \prime \prime }+4 x^{2} y^{\prime \prime }-5 x y^{\prime }+2 y = 30 x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = x^{2}
\] |
✓ |
✓ |
|
\[
{}16 x^{4} y^{\prime \prime \prime \prime }+96 x^{3} y^{\prime \prime \prime }+72 x^{2} y^{\prime \prime }-24 x y^{\prime }+9 y = 96 x^{{5}/{2}}
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime \prime \prime }-4 x^{3} y^{\prime \prime \prime }+12 x^{2} y^{\prime \prime }-24 x y^{\prime }+24 y = x^{4}
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime \prime \prime }+6 x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }-4 x y^{\prime }+4 y = 12 x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-2 x^{2} y^{\prime \prime }+3 x y^{\prime }-3 y = 4 x
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-5 x^{2} y^{\prime \prime }+14 x y^{\prime }-18 y = x^{3}
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-6 x^{2} y^{\prime \prime }+16 x y^{\prime }-16 y = 9 x^{4}
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = x \left (1+x \right )
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime \prime \prime }+3 x^{3} y^{\prime \prime \prime }-x^{2} y^{\prime \prime }+2 x y^{\prime }-2 y = 9 x^{2}
\] |
✓ |
✓ |
|
\[
{}4 x^{4} y^{\prime \prime \prime \prime }+24 x^{3} y^{\prime \prime \prime }+23 x^{2} y^{\prime \prime }-x y^{\prime }+y = 6 x
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime \prime \prime }+5 x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }-6 x y^{\prime }+6 y = 40 x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime \prime }-y^{\prime }-2 y = F \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = F \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-5 y^{\prime \prime }+4 y = F \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime \prime \prime }+6 x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }-4 x y^{\prime }+4 y = F \left (x \right )
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = y_{1} \left (t \right )+2 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )+y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}\left [y_{1}^{\prime }\left (t \right ) = -\frac {5 y_{1} \left (t \right )}{4}+\frac {3 y_{2} \left (t \right )}{4}, y_{2}^{\prime }\left (t \right ) = \frac {3 y_{1} \left (t \right )}{4}-\frac {5 y_{2} \left (t \right )}{4}\right ]
\] |
✓ |
✓ |
|
\[
{}\left [y_{1}^{\prime }\left (t \right ) = -\frac {4 y_{1} \left (t \right )}{5}+\frac {3 y_{2} \left (t \right )}{5}, y_{2}^{\prime }\left (t \right ) = -\frac {2 y_{1} \left (t \right )}{5}-\frac {11 y_{2} \left (t \right )}{5}\right ]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-4 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )-4 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )-3 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )-y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -6 y_{1} \left (t \right )-3 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-2 y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = y_{1} \left (t \right )-y_{2} \left (t \right )-2 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-2 y_{2} \left (t \right )-3 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -4 y_{1} \left (t \right )+y_{2} \left (t \right )-y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -6 y_{1} \left (t \right )-4 y_{2} \left (t \right )-8 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -4 y_{1} \left (t \right )-4 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -8 y_{1} \left (t \right )-4 y_{2} \left (t \right )-6 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 3 y_{1} \left (t \right )+5 y_{2} \left (t \right )+8 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-y_{2} \left (t \right )-2 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-y_{2} \left (t \right )-y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = y_{1} \left (t \right )-y_{2} \left (t \right )+2 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 12 y_{1} \left (t \right )-4 y_{2} \left (t \right )+10 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -6 y_{1} \left (t \right )+y_{2} \left (t \right )-7 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )-y_{2} \left (t \right )-4 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )-3 y_{2} \left (t \right )-2 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = y_{1} \left (t \right )-y_{2} \left (t \right )-y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )+2 y_{2} \left (t \right )-6 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )+6 y_{2} \left (t \right )+2 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )-2 y_{2} \left (t \right )+2 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 3 y_{1} \left (t \right )+2 y_{2} \left (t \right )-2 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )+7 y_{2} \left (t \right )-2 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -10 y_{1} \left (t \right )+10 y_{2} \left (t \right )-5 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 3 y_{1} \left (t \right )+y_{2} \left (t \right )-y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 3 y_{1} \left (t \right )+5 y_{2} \left (t \right )+y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -6 y_{1} \left (t \right )+2 y_{2} \left (t \right )+4 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 3 y_{1} \left (t \right )+4 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -y_{1} \left (t \right )+7 y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-2 y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -7 y_{1} \left (t \right )+4 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-11 y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 3 y_{1} \left (t \right )+y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -y_{1} \left (t \right )+y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )+12 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )-8 y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -10 y_{1} \left (t \right )+9 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -4 y_{1} \left (t \right )+2 y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -13 y_{1} \left (t \right )+16 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -9 y_{1} \left (t \right )+11 y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 2 y_{2} \left (t \right )+y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -4 y_{1} \left (t \right )+6 y_{2} \left (t \right )+y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 4 y_{2} \left (t \right )+2 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}\left [y_{1}^{\prime }\left (t \right ) = \frac {y_{1} \left (t \right )}{3}+\frac {y_{2} \left (t \right )}{3}-y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -\frac {4 y_{1} \left (t \right )}{3}-\frac {4 y_{2} \left (t \right )}{3}+y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -\frac {2 y_{1} \left (t \right )}{3}+\frac {y_{2} \left (t \right )}{3}\right ]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -y_{1} \left (t \right )+y_{2} \left (t \right )-y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )+2 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -y_{1} \left (t \right )+3 y_{2} \left (t \right )-y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )-2 y_{2} \left (t \right )-2 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )+3 y_{2} \left (t \right )-y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )-y_{2} \left (t \right )+3 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 6 y_{1} \left (t \right )-5 y_{2} \left (t \right )+3 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )-y_{2} \left (t \right )+3 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )+y_{2} \left (t \right )+y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -11 y_{1} \left (t \right )+8 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )-3 y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 15 y_{1} \left (t \right )-9 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 16 y_{1} \left (t \right )-9 y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )-4 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-7 y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -7 y_{1} \left (t \right )+24 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -6 y_{1} \left (t \right )+17 y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -7 y_{1} \left (t \right )+3 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )-y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -y_{1} \left (t \right )+y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-y_{2} \left (t \right )-2 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-y_{2} \left (t \right )-y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )+2 y_{2} \left (t \right )+y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )+2 y_{2} \left (t \right )+y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )+3 y_{2} \left (t \right )+2 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -7 y_{1} \left (t \right )-4 y_{2} \left (t \right )+4 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )+y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -9 y_{1} \left (t \right )-5 y_{2} \left (t \right )+6 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-4 y_{2} \left (t \right )-y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 3 y_{1} \left (t \right )+6 y_{2} \left (t \right )+y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )-2 y_{2} \left (t \right )+3 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )-8 y_{2} \left (t \right )-4 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )-y_{2} \left (t \right )-4 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = y_{1} \left (t \right )-y_{2} \left (t \right )+9 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -5 y_{1} \left (t \right )-y_{2} \left (t \right )+11 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -7 y_{1} \left (t \right )+y_{2} \left (t \right )+13 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -4 y_{1} \left (t \right )+8 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 5 y_{1} \left (t \right )-y_{2} \left (t \right )+y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -y_{1} \left (t \right )+9 y_{2} \left (t \right )-3 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )+2 y_{2} \left (t \right )+4 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = y_{1} \left (t \right )+10 y_{2} \left (t \right )-12 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )+2 y_{2} \left (t \right )+3 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )-y_{2} \left (t \right )+6 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -6 y_{1} \left (t \right )-4 y_{2} \left (t \right )-4 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )-y_{2} \left (t \right )+y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )+3 y_{2} \left (t \right )+y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 2 y_{2} \left (t \right )-2 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -y_{1} \left (t \right )+5 y_{2} \left (t \right )-3 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = y_{1} \left (t \right )+y_{2} \left (t \right )+y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )-12 y_{2} \left (t \right )+10 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )-24 y_{2} \left (t \right )+11 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )-24 y_{2} \left (t \right )+8 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-12 y_{2} \left (t \right )+8 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-9 y_{2} \left (t \right )+4 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = y_{1} \left (t \right )-6 y_{2} \left (t \right )+y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -4 y_{1} \left (t \right )-y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-3 y_{2} \left (t \right )-y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = y_{1} \left (t \right )-2 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )-3 y_{2} \left (t \right )+4 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )+5 y_{2} \left (t \right )-8 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )+3 y_{2} \left (t \right )-5 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )-y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-y_{2} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-y_{2} \left (t \right )-2 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -y_{1} \left (t \right )+2 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -5 y_{1} \left (t \right )+5 y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -11 y_{1} \left (t \right )+4 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -26 y_{1} \left (t \right )+9 y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = y_{1} \left (t \right )+2 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -4 y_{1} \left (t \right )+5 y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 5 y_{1} \left (t \right )-6 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 3 y_{1} \left (t \right )-y_{2} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )-3 y_{2} \left (t \right )+y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 2 y_{2} \left (t \right )+2 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 5 y_{1} \left (t \right )+y_{2} \left (t \right )+y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )+3 y_{2} \left (t \right )+y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-5 y_{2} \left (t \right )-3 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )+7 y_{2} \left (t \right )+3 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )+y_{2} \left (t \right )-y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{2} \left (t \right )+y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = y_{1} \left (t \right )+y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[y_{1}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )+y_{2} \left (t \right )-3 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )-y_{2} \left (t \right )+2 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )-2 y_{2} \left (t \right )+3 y_{3} \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\sin \left (t \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+{\mathrm e}^{t^{2}} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 t y = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 t y = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \frac {1}{t^{2}+1}
\] |
✓ |
✓ |
|
\[
{}\cos \left (t \right ) y+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {t}\, \sin \left (t \right ) y+y^{\prime } = 0
\] |
✓ |
✓ |
|